Spatiotemporal analysis of thermal comfort in Azerbaijan - AGAKISHIYEVA, Gunesh; JABRAYILOV, Emil; MAMMADOVA, Jahan (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. Understanding spatiotemporal patterns of thermal comfort is crucial for developing sustainable tourism strategies in geographically diverse regions. This comprehensive study investigates Azerbaijan's complex bioclimatic conditions using the Universal Thermal Climate Index (UTCI), with particular emphasis on how the country's remarkable topographic diversity – ranging from the Caspian coastline to mountain zones – creates distinct microclimates that influence visitor comfort and tourism potential. As climate change continues to alter thermal environments globally, this research provides critical baseline data for adaptive tourism planning in transitional climate zones. Methods. The study employed ERA5-HEAT reanalysis data to calculate UTCI values, incorporating four key meteorological parameters: air temperature, relative humidity, wind speed, and mean radiant temperature. Advanced spatial analysis techniques were implemented using ArcGIS, including interpolation for creating continuous UTCI surfaces, zonal statistics for regional comparisons, and elevation-based corrections using SRTM 30 m DEM data. Results. The analysis revealed extreme annual UTCI variations (–21.0 °C in January highlands to 28.4 °C in August lowlands), demonstrating Azerbaijan's exceptional bioclimatic diversity. Mountainous regions (Greater and Lesser Caucasus) showed prolonged cold stress (UTCI26°C for 60–90 days). Optimal thermal comfort conditions (UTCI 9–26 °C) were most persistent in spring (April–May) and autumn (September–October), particularly at mid-elevations (500–1000 m). Conclusions. This study demonstrates that Azerbaijan's thermal comfort patterns are fundamentally governed by topographic factors. The findings enable precise, climate-responsive tourism planning: cultural and beach tourism in lowlands during shoulder seasons (April–June, September–October), alpine tourism in mountain zones during summer, and winter sports in high-elevation areas. The UTCI-based framework developed here proves particularly valuable for managing thermal stress extremes in both hot and cold environments. These results have immediate practical applications for tourism infrastructure development, seasonal marketing strategies, and climate adaptation planning.
Keywords: UTCI; Azerbaijan; thermal comfort; tourism climatology; sustainable tourism